Food bundling as a health nudge: Investigating consumer fruit and vegetable selection using behavioral economics. (1st February 2018) - Carroll, Kathryn A.; Samek, Anya; Zepeda, Lydia
Abstract: Displaying bundles of healthy foods at the grocery store is a health nudge that simplifies shopping and may have the potential for increasing fruit and vegetable (F&V) purchasing. To evaluate the impact of food bundling, we conduct an artefactual field experiment with community participants in a laboratory set up as a grocery store. Dual-self theory suggests that food choices may differ depending on whether shoppers are under cognitive load – in our experiment, we exogenously vary whether bundles are displayed (with and without a price discount) and whether shoppers are under cognitive load. Our findings align with prior studies that suggest unhealthy options are more likely to be selected when cognitive resources are constrained. When bundles are displayed, we observe increased F&V purchasing. We also observe a significant interaction between cognitive load and price discounting. We find discounted bundles are more effective in the absence of cognitive load, but non-discounted bundles are more effective when shoppers are under cognitive load. Although more research is warranted, our findings suggest that when shopping under cognitive load, it is possible that discounts impose additional cognitive strain on the shopping experience. For retailers and policymakers, our results point to the potential power of bundling as a strategy for increasing healthy food purchasing.